RASIONALISASI PEMANFAATAN DANA ZIS DALAM UPAYA MEMBANGKITKAN KESADARAN UMAT (STUDI LAZNAS PADA KOTA MAKASSAR) - Masyhuri Masyhuri (Islamic Banking and Finance, 2021)
ABSTRACT Utilization of ZIS Funds in Economic Empowerment of the People in Makassar City. The purpose of this study is to: (1) analyze the concept of using ZIS funds by the Amil Zakat Institution (LAZNAS) in empowering mustahik in empowered villages assisted by Rumah Zakat in Makassar city. (2) analyzing the Mustahik Empowerment Concept in Islamic Philanthropy in Reducing Poverty. (3) to find out the Inhibiting Factors and Challenges of Rumah Zakat in Empowering Mustahik in Makassar City in the empowered village of Rumah Zakat Representative of South Sulawesi. This study uses a qualitative approach based on the interpretive paradigm ofwithout using interviews. The data were analyzed using the Miles and Huberman model, which included the data reduction stage, the data display stage, and the conclusion drawing/verification stage. The results of this study indicate that the concept of using ZIS funds in empowering the people's economy and the concept of empowering mustahik in reducing poverty in the assisted villages of zakat houses in Makassar city have been carried out well. Although there are still some obstacles that need to be addressed, namely the existence of a production house as a center for economic empowerment of the people, product marketing innovations for mustahiq members, and collaboration with all levels of society. Keywords: Accountability, Utilization of ZIS Funds, Amil Zakat Institutions (LAZNAS), Concept of People's Economic Empowerment, Poverty